Thinking the "unthinkable": why Philip Morris considered quitting. Issue 2 (1st June 2003) - Smith, E A; Malone, R E
Abstract : Objective: To investigate the genesis and development of tobacco company Philip Morris's recent image enhancement strategies and analyse their significance. Data sources: Internal Philip Morris documents, made available by the terms of the Master Settlement Agreement between the tobacco companies and the attorneys general of 46 states, and secondary newspaper sources. Study selection: Searches of the Philip Morris documents website (www.pmdocs.com ) beginning with terms such as "image management" and "identity" and expanding as relevant new terms (consultant names, project names, and dates), were identified, using a "snowball" sampling strategy. Findings and conclusions: In the early 1990s, Philip Morris, faced with increasing pressures generated both externally, from the non-smokers' rights and public health communities, and internally, from the conflicts among its varied operating companies, seriously considered leaving the tobacco business. Discussions of this option, which occurred at the highest levels of management, focused on the changing social climate regarding tobacco and smoking that the tobacco control movement had effected. However, this option was rejected in favour of the image enhancement strategy that culminated with the recent "Altria" name change. This analysis suggests that advocacy efforts have the potential to significantly denormalise tobacco as a corporate enterprise.